2017
DOI: 10.3847/1538-4357/aa80db
|View full text |Cite
|
Sign up to set email alerts
|

Star Formation Activity of Barred Spiral Galaxies

Abstract: We study the star formation activity of nearby galaxies with bars using a sample of late-type galaxies at 0.02≤ z ≤ 0.05489 and M r < −19.5 from the Sloan Digital Sky Survey. We compare the physical properties of strongly and weakly barred galaxies with those of non-barred galaxies that have stellar mass and redshift distributions similar to barred galaxies. We find that the star formation activity of strongly barred galaxies probed by starburstiness, g − r , NUV−r, and mid-infrared [3.4]−[12] colors is, on av… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 77 publications
4
23
1
Order By: Relevance
“…However, while we indeed observe a higher fraction of CO-only sight lines in grand-design spiral galaxies (Figure 6), the CO-only fractions of Bar and Bar+GD are comparable to NS galaxies. It is probably because we do not consider bar strength in this work which is known to be correlated with SFR and star formation history of galaxies (Martinet & Friedli 1997;Carles et al 2016;Kim et al 2017). An alternative explanation could be that the gas distribution in barred galaxies is evolving heavily over time (e.g., Donohoe-Keyes et al 2019), leading to a wide variety in the gas distribution in the barred galaxies seen in PHANGS (Leroy et al 2021b).…”
Section: Effect Of Galactic Dynamicsmentioning
confidence: 99%
“…However, while we indeed observe a higher fraction of CO-only sight lines in grand-design spiral galaxies (Figure 6), the CO-only fractions of Bar and Bar+GD are comparable to NS galaxies. It is probably because we do not consider bar strength in this work which is known to be correlated with SFR and star formation history of galaxies (Martinet & Friedli 1997;Carles et al 2016;Kim et al 2017). An alternative explanation could be that the gas distribution in barred galaxies is evolving heavily over time (e.g., Donohoe-Keyes et al 2019), leading to a wide variety in the gas distribution in the barred galaxies seen in PHANGS (Leroy et al 2021b).…”
Section: Effect Of Galactic Dynamicsmentioning
confidence: 99%
“…Tubbs 1982;Kim et al 2018). Kim et al (2017), using a large sample of galaxies from Averaged star formation rate from the Hα line (left columns), the Hα emission from the H ii region only, (middle columns) and from the FUV continuum (right columns). The total sample was divided into several samples: Sm and dS (upper rows), barred and nonbarred galaxies (middle rows), and barred/non barred Sm and dS (bottom rows).…”
Section: Bars and Star Formation Ratesmentioning
confidence: 99%
“…Tubbs (1982) proposed the probability of a decrease in total starforming rates due to bars in the galaxy. Kim et al (2017) showed that there is a significantly lower star-forming activity of strongly-barred galaxies than their unbarred counterparts. The SDSS optical image of the galaxy UGC 2604 is shown in Fig.…”
Section: Region Of Interestmentioning
confidence: 99%